Modeling of in-utero and intra-partum transmissions to evaluate the efficacy of interventions for the prevention of perinatal HIV - Patumrat Sripan (2018)
Copyright © 2015 Sripan et al. Background Antiretroviral treatments decrease HIV mother-to-child transmission through pre/post exposure prophylaxis and reduction of maternal viral load. We modeled in-utero and intra-partumHIV transmissions to investigate the preventive role of various antiretroviral treatments interventions. Methods We analysed data from 3,759 women-infant pairs enrolled in 3 randomized clinical trials evaluating (1) zidovudine monotherapy, (2) zidovudine plus perinatal single-dose nevirapine or (3) zidovudine plus lopinavir/ritonavir for the prevention of mother-to-child transmission of HIV in Thailand. All infants were formula-fed. Non-linear mixed effect modeling was used to express the viral load evolution under antiretroviral treatments and the probability of transmission. Results Median viral load was 4 log10 copies/mL (Interquartile range: 3.36-4.56) before antiretroviral treatments initiation. An Emaxmodel described the viral load time-course during pregnancy. Half of the maximum effect of zidovudine (28%decrease) and lopinavir/ritonavir (72%decrease) were achieved after 98 and 12 days, respectively. Adjusted on viral load at baseline (Odds ratio = 1.50 [95%confidence interval: 1.34, 1.68] per log10 copies/mL increment), antiretroviral treatments duration (OR = 0.80 [0.75, 0.84] per week increment) but not the nature of antiretroviral treatments were associated with in-utero transmission. Adjusted on gestational age at delivery ( < 37 weeks, OR = 2.37 [1.37, 4.10]), baseline CD4 (Odds ratio = 0.79 [0.72, 0.88] per 100 cells/mm < sup > 3 < /sup > increment) and predicted viral load at delivery (OR = 1.47 [1.25, 1.64] per log10 copies/mL increment), single-dose nevirapine considerably reduced intra-partum transmission (OR = 0.32 [0.2, 0.51] ).